A prospective study of laproscopic paravaginal repair of cystocoele: our experience - Gosavi, Amrapali D.; Dhangar, Sanjay P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Cystocele is diagnosed clinically by vaginal examination approaches using the pelvic organ prolapse quantifications system (POP-Q) of classification. Abdominal and laproscopic are now used due to high failure rate involving the transvaginal repair. Laproscopic repair involves approximation of the vaginal sub-epithelial tissue with the Cooper’s ligament using non-absorbable suture. Methods: This was a prospective observational study from June 2016 to May 2020 over women with symptomatic cystocele of grade ≥2. All patients were preoperatively and post-operatively assessed with quality-of-life questionnaires, pelvic organ prolapse distress inventory-6 (POPDI-6) and urinary distress inventory short form. Clinical examination was done with and without Valsalva maneuver. POP classification was used for grading the prolapse. All patients were assessed for any voiding difficulty after surgery, at one week, three months, six months and 12 months. Results: The median age of patient was 55.5 years. 90.9% patients presented with urinary symptoms. 54.5% patients underwent hysterectomy. The mean blood loss was 55 cc. The anatomic cure rate for cystocoele was 100% in our study in 1 week, 3 months and 6 months post-operatively. There was significant improvement in the quality-of-life scores. Overall, symptomatic relief was seen in 90.9% patients at first week, 95.4% at 3 months, 95.4% at 6 and 12 months follow up. Urinary symptoms were relieved in all patients at first follow up after 7 days, and 95.4% patients during 3, 6 and 12 months follow up. Conclusions: Laproscopic paravaginal cystocoele repair is safe, effective and an easy procedure with good results. The procedure is easy to learn and master with low recurrence rates.